Local Leader-Based Early Marriage Prevention Intervention - Maida Pardosi; Elisabeth Surbakti; Efendi Sianturi (Indonesian Journal of Global Health Research, 2025)
Early marriage causes early pregnancy and childbirth, which are associated with high maternal mortality rates, pregnancy and childbirth complications, Low Birth Weight, and stunting. The study aimed to improve adolescent knowledge and attitudes about early marriage by empowering local leaders in Tambak Bayan Hamlet, Saentis Village, and Deli Serdang Regency. This study is quasi-experimental. It aims to improve the knowledge and attitudes of adolescents about preventing early marriage. Trained Local leaders carry out Health Promotion. Pre- and post-tests were carried out to evaluate the impact of health promotion on adolescents, and 50 adolescent samples were used. Data analysis with the Paired T-test If the data follows a normal distribution, a parametric test is used; conversely, if the data does not adhere to a normal distribution, the Wilcoxon test is applied. Data analysis using the Paired T-test if the data is usually distributed and if the data is not normally distributed, the Wilcoxon test is used. This study showed increased adolescent knowledge and attitudes about early marriage (p-value <0.05). The conclusion is that nderstanding early marriage can be used to create adolescent maturation programs, avoiding protecting society from the dangerous consequences of early marriage.